Urinary incontinence in elderly women from Porto Alegre: its prevalence and relation to pelvic floor muscle function (Fisioterapia e Pesquisa, 2014)
The purpose of this cross-sectional study was to assess the prevalence of self-reported urinary loss in elderly women living in the city of Porto Alegre (Rio Grande do Sul, Brazil), as well as to determine the relation between urinary incontinence (UI) and pelvic floor muscle function (PFMF). It included 270 elderly women (aged from 60 to 92 years) from a population sample, who reported the presence (n=155; 69.1±7.8 years) or absence (n=115; 67.7±7.9 years) of urine loss. Those who reported UI were asked about how long they had been experiencing urinary leakage, the amount of urine lost (drops, jets or complete micturition) and situations in which they lost urine. Out of the total number of individuals, 178 agreed to undergo the assessment of PFMF by means of a perineometry and a bidigital test. The prevalence of elderly women who reported UI (57.4%) was significantly higher, and the most common isolated situation of urine loss was being unable to get to the toilet in time (26.1%), and this occurred mainly in drops (52.3%). The UI lasted for a median of three years. The elderly women with UI had significantly lower PFMF than those without it, regardless of the type of measurement used (perineometry or bidigital test). Therefore, we conclude that, in this sample, UI had a high prevalence and was associated with decreased PFMF. Bearing these findings in mind and taking into account the data available in the literature about the impact of UI on health and quality of life, as well as the low cost of its assessment and treatment, we suggest that the management and care of this dysfunction should be carried out at the Primary Health Care level.